Analysis of Online Learning Applications During The Covid-19 Pandemic - Huda, Syafaat Ariful; Jaenudin, Jaenudin; Muqtashid, Amry; Widiatna, Alexius Dwi; Nababan, Holong Saor (UNDIKMA, 2023)
This study aims to analyze the perceptions of English language education students towards applications that are used effectively and the most effective applications for online learning in the era of the Covid-19 pandemic. This research uses the SEM (Structural Equation Modeling) method. The subjects of this study were 105 sixth-semester students of English Language Education at UIN Sultan Maulana Hasanudin Banten. The instrument used in this study was a questionnaire. Analyze data using descriptive statistics and structural equation modeling in inferential statistics. The findings showed that students had a positive or positive perception of effective applications for online learning during the Covid-19 pandemic. Based on the findings, it can be seen that the application used by students in online learning in this pandemic era is very effective because the distance learning process has become easier with the application. Then 77% of respondents said that the most efficient application used in online learning is Google Meet because, technically, Google Meet is easier to use, does not require much internet costs, does not interfere when online learning, and is convenient to use.